Low Level of Dietary Organic Trace Elements Improve the Eggshell Strength, Trace Element Utilization, and Intestinal Function in Late-Phase Laying Hens - Chen, Xing; Ma, Xiang-ming; Yang, Chong-Wu; Jiang, Shu-zhen; Huang, Li-bo; Li, Yang; Zhang, Fan; Jiao, Ning; Yang, Wei-ren (Frontiers in Veterinary Science, 2022)
This study was conducted to evaluate the effects of organic trace elements (Cu, Fe, Zn and Mn) on performance, egg quality, trace elements utilization and intestinal function in late-phase laying hens. A total of 1080 laying hens (Hy-line brown, 65 wk old) were randomly assigned to four treatments with six replications of 45 layers each. The basal diet was prepared without adding exogenous trace elements. The control group was fed with basal diet supplemented with 600 mg/kg inorganic trace elements. The three treatment groups were fed basal diets supplemented with 300, 450 and 600 mg/kg organic trace elements (OTE300, 450, 600), respectively. The results showed that there was no significant difference in growth performance among all treatments. However, OTE450 significantly improved the eggshell strength of laying hens (P < 0.05), but had no significant effects on Harding unit, egg yolk weight, eggshell weight and eggshell thickness, compared with other groups. Moreover, compared with the control group, OTE450 significantly increased the contents of copper, iron and zinc in serum (P < 0.05). Meanwhile, all of the trace elements had a lower deposition in the feces in organic trace elements groups (P < 0.05). Histological analysis showed that the addition of organic trace elements could significantly improve the villus height and villus concealment ratio (P < 0.05). In addition, the mRNA and protein expressions of DMT1, ZnT-1 and FPN1 were the highest in OTE450 group. In conclusion, OTE450 could improve egg quality, intestinal function and trace element utilization efficiency. Thus, this study provides a theoretical basis for the application of low level of organic trace elements in laying hens.